The 4 disciplines of execution achieving your wildly important goals - McChesney, Chris (New York Free Press, 2012)
The 4 Disciplines of Execution offers?the ?what? but also ?how? effective execution is achieved. They share numerous examples of companies that have done just that, not once, but over and over again. This is a book that every leader should read!? (Clayton Christensen, Professor, Harvard Business School, and author of The Innovator?s Dilemma).
Includes bibliographical references and index.
Keywords: Goal setting in personnel management